SIFAT KIMIA TANAH DAN KESESUAIAN LAHAN PADA MASING-MASING TIPOLOGI LAHAN RAWA LEBAK UNTUK BUDIDAYA TANAMAN PADI, KASUS DI DESA TANJUNG ELAI, OGAN KOMERING ILIR - Waluyo, Waluyo; Djamhari, Sudaryanto (Jurnal Sains dan Teknologi Indonesia, 2011)
Research conducted in the village of Tanjung Alai, District of Padang Sira Island Komering Ogan Ilir district of South Sumatra with an area of 100 ha. This study aims to determine the soil chemical properties and suitability of land in each valley swamp land typology. Result interpretation and field observation and analysis of soil samples, the soil in the study area can be categorized as follows: 1) Typic Haplosaprists; saprik, shallow, drainage is blocked, flat pH 4.6, covering 13.5 hectares or 13.5%. 2) Humic Endoaquent; texture of clay dust layer, bottom layer of clay, deep, drainage is blocked, flat, pH 4.6, an area of 11.5 ha or 11.5%. 3)Humic Endoaquent; texture of clay dust layer, bottom layer of clay to sandy clay, in, blocked drainage, flat, pH 4.4 to 4.6, an area of 45 ha or 45%. 4) Typic Dystrudepts; texture of clay dust layer, bottom layer of sandy clay, deep drainage was, flatly, pH 6.0, an area of 30 ha or 30%.Based on the parameters used in determining the suitability of land that is effective depth, soil fertility, soil acidity, drainage class, damage due to flooding and others, it can be divided into 3 units of land for land suitability for rice paddy fields as follows: 1), S2ra-1 (paddy rice).Enough suitable land for paddy rice crops, the rooting medium limiting factor (saprik peat maturity) and the retention of nutrients (acid soil pH), an 13.5 ha (13.5%) for rice fields. 2). S2ra-2 (paddy rice); Enough suitable land for paddy rice crops, the rooting medium limiting factor (dusty clay texture) and nutrient retention (acid soil pH), an area of 56.5 ha (56.5%) for rice paddies. 3) N2d (soy), S3r2 (paddy rice); Marginal land suitable for paddy rice crop, with the limiting factor rooting medium (somewhat hampered drainage).